The Effect of Perceived Convenience, Service Quality, and OVO Cashback Promotion on Consumer Satisfaction in Students of the Faculty of Economics - Rania Tabita Br Sebayang; Winda Sri Astuti Doloksaribu; Vivi Acela Br Sembiring; Lukas Kodrat Ardoman Bali; Kevin Irving Edward Nadapdap (SEAN Institute, 2022)
This research aims to find out how the effect of The Convenience Perception, Cashback Promo, and Quality of Service on Customer Satisfaction in Students of Universitas Prima Indonesia. This study used the SPSS application. In this study, the population used at Universitas Prima Indonesia was 93 students. The method used in this research is a quantitative approach. The results of this study variable Ease Perception have a positive and significant effect on Customer Satisfaction with a significance of 0.000 and thitung 5.223. Cashback Promo variables have a positive and significant effect on Customer Satisfaction with a significance of 0.000 and thitung 5,922. Service Quality variables have a positive and significant effect on Customer Satisfaction with a significance of 0.000 and thitung 5,678. Variables of Ease, Completion, and Quality of Service Precepts simultaneously affect Customer Satisfaction.